The genetics of adaptation in freshwater Eurasian shad (Alosa) - Stephen J. Sabatino; Paulo Pereira; Miguel Carneiro; Jolita Dilytė; John Patrick Archer; Antonio Munoz; Francesco Nonnis‐Marzano; Antonio Murias (Ecology and Evolution, 2022)
Abstract Studying the genetics of phenotypic convergence can yield important insights into adaptive evolution. Here, we conducted a comparative genomic study of four lineages (species and subspecies) of anadromous shad (Alosa) that have independently evolved life cycles entirely completed in freshwater. Three naturally diverged (A. fallax lacustris, A. f. killarnensis, and A. macedonica), and the fourth (A. alosa) was artificially landlocked during the last century. To conduct this analysis, we assembled and annotated a draft of the A. alosa genome and generated whole‐genome sequencing for 16 anadromous and freshwater populations of shad. Widespread evidence for parallel genetic changes in freshwater populations within lineages was found. In freshwater A. alosa, which have only been diverging for tens of generations, this shows that parallel adaptive evolution can rapidly occur. However, parallel genetic changes across lineages were comparatively rare. The degree of genetic parallelism was not strongly related to the number of shared polymorphisms between lineages, thus suggesting that other factors such as divergence among ancestral populations or environmental variation may influence genetic parallelism across these lineages. These overall patterns were exemplified by genetic differentiation involving a paralog of ATPase‐α1 that appears to be under selection in just two of the more distantly related lineages studied, A. f. lacustris and A. alosa. Our findings provide insights into the genetic architecture of adaptation and parallel evolution along a continuum of population divergence.